The Role of Bhabinkamtibmas in Preventing Radicalism in the Jurisdiction of the Bandung Polrestabes - Hardyanto, Aditya (Indonesian Journal of Police Studies, 2024)
This research is motivated by the widespread spread of radical flow in the jurisdiction of Polrestabes Bandung. This study aims to explain the picture of radicalism in the Bandung police region, explain the role of Bhabinkamtibmas in efforts to prevent radicalism in the Bandung police region and analyze the factors that influence the role of Bhabinkamtibmas in the effort to prevent radicalism in the Bandung police region. The theory used in this research is role theory, the concept of community policing, the concept of radicalism, crime prevention models, development of crime prevention strategies and SWOT analysis. The method used in this research is the field research method. The results of this study indicate that the development of radical understanding in the legal area of the Bandung Polrestabes comes from 4 groups namely ISIS, HTI, Liberation Echo, and GAFATAR, the role of Bhabinkamtibmas in preventing radicalism is carried out with a soft power approach in the form of de-radicalization activities, and the factors that influence the role Bhabinkamtibmas in the prevention of radicalism which in the jurisdiction of Bandung Polrestabes comes from internal and external factors. Suggestions given from the results of this study include counseling de-radicalization to schools, mosques and activities carried out by Bandung community groups, as well as improving the quality of education in Bandung society.